Gynaecological surgery. (11th December 2018) - Chien, Patrick
Abstract : Deputy Editor‐in‐Chief, Dr Patrick Chien, discusses his top articles from this issue in an audio podcast available at:https://soundcloud.com/bjog/january-editorial-2019